Accessibility of healthcare in rural Zimbabwe: The perspective of nurses and healthcare users - Manenji Mangundu; Lizeth Roets; Elsie Janse van Rensberg (African Journal of Primary Health Care & Family Medicine, 2020)
Background: Accessibility of healthcare in rural areas is globally impeded by physical, material, human, financial and managerial resources and societal barriers in the healthcare system. Developing countries like Zimbabwe are significantly affected. Aim: The aim of this article was to share the perspectives of nurses and healthcare users (HCUs) in the rural areas of Zimbabwe with regard to the accessibility of healthcare. Setting: The study was conducted at 45 rural health facilities in Chegutu district, Mashonaland West province and Masvingo district in Masvingo province, Zimbabwe. Methods: A self-administered questionnaire (for professional nurses) and a structured interview questionnaire (for HCUs) were utilised to gather data in a cross-sectional survey. Two districts were randomly sampled from 59 districts. All nurses working in 45 public health facilities in the selected two districts, who were willing and available to participate, were included. Ninety nurses participated in the study. The HCUs were selected through a multistage sampling technique. The sample size for HCUs was calculated by using Dobson’s formula, and 445 HCUs were included via convenience sampling. Results: Nurses reported challenges such as work overload because of staffing shortages (55%) and the supply of necessary medical drugs that lacked consistency in both the quantity and type ordered(46.7%). The challenges faced by HCUs included long distances from villages to health facilities (86%), unaffordability of transport costs and lack of access to medical drugs (59.95%), causing them to seek assistance from traditional healers (43%). Conclusion: Both the nurses and HCUs perceived grave challenges regarding access to health facilities, health workers and medical drugs, all of which are bound to have an impact on the health of communities in rural Zimbabwe.